The Effect of Ultrasonic Treatment on Thermal Stability of the Cured Epoxy/Layered Silicate Nanocomposite - N. Y. Yuhana; S. Ahmad; A. R. Shamsul Bahri (Advances in Materials Science and Engineering)
The effect of ultrasonic treatment on thermal stability of binary systems containing epoxy and organic chemically modified montmorillonite (Cloisite 30B) was studied. Differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), transmission electron microscopy (TEM), and wide angle X-ray diffraction (WAXD) analysis were utilized. The mixing of epoxy and Cloisite 30B nanocomposites was performed by mechanical stirring, followed by 1 or 3-hour ultrasonic treatment, and polyetheramine as the curing agent. Both XRD and TEM analyses confirmed that the intercalation of Cloisite 30B was achieved. The d0 spacings for silicate in cured sample prepared at 1- and 3-hour duration of ultrasonic treatment were about 21 and 18 Å, respectively. This shows that shorter duration or ultrasonic treatment may be preferable to achieve higher d0 spacing of clay. This may be attributed to the increase in viscosity as homopolymerization process occurred, which restricts silicate dispersion. The 1-hour sonicated samples seem to be more thermally stable during the glass transition, but less stable during thermal decomposition process.